Supercritical extraction of betalains from the peel of different pitaya species - Lacerda, Vander Rocha [UNESP]; Bastante, Cristina Cejudo; Machado, Noelia D.; Vieites, Rogério Lopes [UNESP]; Casas Cardoso, Lourdes; Mantell-Serrano, Casimiro (Wiley, 2024)
BACKGROUND: Pitaya is a fruit with high consumer acceptance and health benefits. Pitaya peel is a waste product with potential in the food industry, as an antioxidant enrichment and natural colouring. Therefore, there is an interest in recovering its constituents and searching for pitaya species with greater potential. This work aimed to obtain bioactive extracts from the dried peel of pitaya fruits of the species Selenicereus monacanthus (Lem.), S. costaricensis W. and S. undatus H. using supercritical fluids at different pressures (100, 250 and 400 bar) and ethanol–water 15% v/v or ethanol 100% as co-solvents. The extraction yield, antioxidant activity, colour and total betalain content were evaluated. RESULTS: The extract obtained from S. monacanthus showed the highest extraction yield (49.6 g kg−1), followed by S. costaricensis (27.5 g kg−1) and S. undatus (17.7 g kg−1) at 400 bar and 35 °C using ethanol 15%, v/v. The antioxidant capacity was strongly influenced by pressure, favouring the obtaining of betalain-rich extracts at higher pressures, especially in the species S. costaricensis (0.6 g kg−1) and S. monacanthus (0.3 g kg−1). To improve the extraction of S. undatus (the most cultivated species), the procedure of subsequential extractions was applied. This procedure considerably increased the extraction yield, antioxidant activity and total content of betalains. The use of ethanol 100% provided more bioactive fractions and achieved a good separation of betalains. CONCLUSION: The supercritical extraction method can overcome the challenge of efficiently extracting compounds from pitaya peel, due to the presence of bioactive compounds of great polarity. © 2024 Society of Chemical Industry.
Keywords: antioxidant activity; betalains; dragon fruit; Selenicereus spp.